Sorption of vanadium (V) on three typical agricultural soil of the Loess Plateau, China. Issue 1 (1st January 2019) - Jiang, Yanji; Yin, Xianqiang; Luo, Xiuhua; Yu, Lin; Sun, Huimin; Wang, Nong; Mathews, Shiny
ABSTRACT: Selected three soil (yellow cinnamon soil, manual loessial soil and aeolian sandy soil) to study the kinetics and isotherms sorption of V(Ⅴ), and further explore the differences in the adsorption mechanism caused by initial V (V) concentration, ionic strength (IS), pH and different reaction times. It was observed that V(Ⅴ) adsorption onto the soil had three processes and completed rapid adsorption in 60, 100 and 120 min. The maximum adsorbing capacity of V(Ⅴ) on yellow cinnamon soil, manual loessial soil and aeolian sandy soil reached stable in pH range from 4 to 8. The adsorption capacity decreased with the increase of IS. V(Ⅴ) adsorption onto soil varied greatly with mineralogy and properties of soil, the surface area, soil organic carbon content and composition of particulate matter. This research enhanced the understanding of how soil properties affect vanadium (V) sorption onto agricultural soil.To investigate the reaction mechanism between vanadium (Ⅴ) and soil, and further explore the differences in the adsorption mechanism caused by initial V(V) concentration, ionic strength, pH and different reaction times. Selected three soil (yellow cinnamon soil, manual loessial soil and aeolian sandy soil) which are the typical agricultural soil from Shaanxi province to study the kinetics and isotherms sorption of V(Ⅴ). SEM study is used to probe the morphological features of the soil in the presence of vanadium and to investigate the change of surface functional groups on the three soils after adsorption by the FTIR spectra. It was observed that V(Ⅴ) adsorption onto the soil had three processes and completed rapid adsorption in 60 min, 100 min and 120 min. The maximum adsorption concentration of V(Ⅴ) derived from experimental data for the yellow cinnamon soil, manual loessial soil and aeolian sandy soil were 1124.6mg kg, 854.4mg kg and 748.6mg kg, respectively. The maximum adsorbing capacity of V(Ⅴ) on yellow cinnamon soil, manual loessial soil and aeolian sandy soil reached stable in the pH range from 4.0 to 8.0. The adsorption capacity decreased with the increase of ionic strength. V(Ⅴ) adsorption onto soil varied greatly with mineralogy and physical–chemical properties of soil, the BET surface area, soil organic carbon content and composition of particulate matter. This research enhanced the understanding of how soil properties affect vanadium (V) sorption onto agricultural soil.